How can digitalization be used to develop community resilience in public health emergencies?: A qualitative comparative analysis from China. - Liqing Li; Zihan Li; Haifeng Ding; Meng Gao (PLoS ONE)
Community resilience is critical for the government's response to public health emergencies. With the rapid development of digital technology, leveraging digital tools for grassroots community governance has become increasingly important for the Chinese government. Fuzzy set qualitative comparative analysis (fsQCA) is utilized in this study to establish a framework for investigating the historical development of holistic intelligent governance for community resilience in the context of public health emergencies. Using 31 provincial-level regions in mainland China as research samples and taking the development of community resilience as the outcome variable, the study explores the configurational models and developmental pathways of holistic intelligent governance in enhancing community resilience from a conditional configurational perspective. The results of this study suggest that the mechanisms of community resilience in the face of public health emergencies revolve around five key factors: community self-organization legitimacy, grassroots party-building leadership, policy support, digital governance platform funding, and organizational digitization. However, no single variable alone constitutes a necessary condition for fostering community resilience. Instead, a combination of these factors is required, along with other variables promoting the formation of community resilience, among which community self-organizational legitimacy, grassroots party-building leadership, digital governance platform funding, and organizational digitization serve as the productive basis for promoting the formation of community resilience in holistic intelligent governance at the grassroots level, and are complementary to policy support.